Pakistan's lady health worker labor movement and the moral economy of heroism. Issue 1 (May 2015) - CLOSSER, SVEA; Maes, Kenneth
<x xml:space="preserve">Abstract</x> In December 2012, militants began targeted attacks on workers going door to door in Pakistan delivering polio vaccine, including members of a community health worker cadre called Lady Health Workers (LHWs). Over the next several years, more than 50 workers, most of them women, were murdered as they worked. Media accounts frequently refer to these workers as "aid workers" or "heroes." This paper complicates and theorizes this conception. Two conflicting moral economies around the work of LHWs existed before the targeted killings began; both have amplified since. One, shared among the LHWs themselves, centers around ideas of community health work as deserving of remuneration just like other government work. The other, promoted by the Global Polio Eradication Initiative at the international level, conceptualizes ground level workers like LHWs as "heroes, " not as labor—eclipsing the LHWs' own discourse in the international sphere.